Multiculturalism in transit a German-American exchange - Milich, Klaus J.; Peck, Jeffrey M., 1950- (New York : Berghahn Books, 1998)
"Multiculturalism is a controversial topic both in the United States and in Germany. This interdisciplinary collection of essays by German scholars in American Studies and American scholars in German Studies analyzes the "other" from this dual perspective and from disciplines such as literary and cultural studies, political science, anthropology, and history. More particularly they examine multiculturalism in terms of national and ethnic identities, as well as gender and race, and look at the disciplines and institutions that produce and legitimize discourses on subjects such as minority literatures, feminism, and the notion of foreignness itself. What becomes clear in this volume is that careful attention must be paid to the particular conditions and varying ideological concepts that shape the term multiculturalism, i.e., the "national" historical, political, social, and institutional contexts in which it appears, circulates, and accrues meanings."--BOOK JACKET.
Foreword / Dieter Dettke -- Introduction / Klaus J. Milich and Jeffrey M. Peck -- I. Theorizing Comparisons. 1. The Uses of Comparison / Gisela Welz. 2. Race, Color ... and Creed / Timothy Brennan. 3. The Politics of Difference: Theories and Practice in a Comparative U.S.-German Perspective / Berndt Ostendorf -- II. Gender and Race -- Two Categories of Multiculturalism. 4. Gender in a Transatlantic Perspective / Renate Hof. 5. Feminisms in Transit: American Feminist Germanists Construct a Multicultural Germany / Sara Lennox. 6. The Germanification of Black Women's Literature / Anne Koenen -- III. American Studies in Germany -- German Studies in America. 7. Multiculturality in the German Democratic Republic and the Reception of African-American Literature / Friederike Hajek. 8. American Studies East and West: A Multicultural Project? / Catrin Gersdorf. 9. Transnational American Studies: Negotiating Cultures of Difference -- Multicultural Identities, Communities, and Border Discourses / Gunter H. Lenz. 10. Multiculturalism and the European Connection: Theme Park or Dual Citizenship? / Frank Trommler. 11. Inventing the Nation: Literary Study As a Discipline of Identity / Hinrich C. Seeba -- IV. Multiculturalism in the Transatlantic Sphere. 12. Geographies of Memory: Protocols of Writing in the Borderlands / Azade Seyhan. 13. The Transatlantic Ties of Cultural Pluralism -- Germany and the United States: Horace M. Kallen and Daniel Cohn-Bendit / Alfred Hornung. 14. Wong Kim Ark and the Determination of United States Citizenship / Brook Thomas. 15. The Discourse of Differentiation: German Political Membership / Gregg O. Kvistad. 16. Multiculturalism, Nationalism, and the Political Consensus in the United States and in Germany / Hans-Jurgen Puhle.
JSTOR
Keywords: Cultural pluralism -- United States; Cultural pluralism -- Germany; United States -- Relations -- Germany; Germany -- Relations -- United States; United States -- Ethnic relations; Germany -- Ethnic relations; Diversité culturelle -- États-Unis.; Diversité culturelle -- Allemagne; États-Unis -- Relations interethniques; SOCIAL SCIENCE / General; Cultural pluralism; Ethnic relations; International relations; Germany; United States; Amerikaforschung; Internationaler Vergleich; Multikulturelle Gesellschaft; Aufsatzsammlung; Deutschland; USA; Multiculturele samenlevingen